PvdA-bijeenkomst: Verkiezingen en derde wereld.V.l.n.r. : Kombrink, Van der Spek, ?, Brinkhorst, Van Bladel, Beckers, ? - Stegeman, Jan,
PvdA-bijeenkomst: Verkiezingen en derde wereld.V.l.n.r. : Kombrink, Van der Spek, ?, Brinkhorst, Van Bladel, Beckers, ?.